Menilik “Tilik”: Representasi Citra Perempuan Dalam Transformasi Ruang Virtual - Putri, Addin Kurnia; Wibisono, Gunawan (Indonesian Democracy Research Center, 2022)
As part of popular culture products, movies play an important role in shaping images and representations in social life. A movie always captures the social reality that develops in society. Exploring the meaning of movie texts can be done from various perspectives.